Methane concentration and oxidation rate in the Yangtze River Estuary (July 2021) and East China Sea (April 2021) - Shi-Hai Mao; Hong-Hai Zhang; Guang-Chao Zhuang; Xiao-Jun Li; Qiao Liu; Zhen Zhou (PANGAEA, 2022)
We investigated the dynamic of methane (CH4) concentration, saturation, and sea-to-air flux in the typical near-shore (Yangtze River Estuary) and outer shelf (East China Sea) areas. We further determined the dynamic of aerobic methanotrophic activity employing in vitro radiotracer assay. The data presented here are beneficial to advancing our understanding for the methane cycle in the estuarine and shelf regions. Water samples were collected from the Yangtze River Estuary and East China Sea aboard the R/V “Runjiang 1 and Zheyuke 2”, “Xiangyang hong 18” during three expeditions in July and March-April 2021. Methane samples were collected directly using a 12 L Niskin bottle deployed on a Seabird 911 CTD rosette system, from which seawater temperature, salinity and depth were recorded. Methane samples in seawater were measured using a cryogenic purge-and-trap setup connected to an Agilent GC-8890 gas chromatograph with a flame ionization detector according to the detailed methods given in (Zhang et al., 2004). We used a radiotracer approach and added 3H-CH4 to seawater samples to determine the methan oxidation (MOx) rate by quantifying 3H-CH4 oxidation to 3H-H2O (Rogener et al., 2020).